PENGARUH EKSPEKTASI PENDAPATAN, KEPRIBADIAN, DAN PENGETAHUAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA PROGRAM STUDI AKUNTANSI UNIVERSITAS TADULAKO - Hamsun, Hamsun; Natsir, Muh; Mile, Yuldi; Yuniar, Latifah Sukmawati (Jurnal Akun Nabelo : Jurnal Akuntansi Netral, Akuntabel, Objektif, 2019)
This study aims to test and analyze the Effect of Income Expectations, Personality, and Entrepreneurship Knowledge on the Interest of Entrepreneurial Students in the Accounting Study Program at Tadulako University. The data used in this study are primary data. Primer data used in the form of questionnaires as much as 80. Data analysis techniques using multiple regression analysis with the help of SPSS 22.0 for Windows. The results of this study indicate that simultaneously Income Expectations, Personality, and Entrepreneurship Knowledge have a significant effect on Entrepreneurial Interest. The results of this study indicate that, Income Expectations and Personality, have a significant effect on Entrepreneurial Interest. while Entrepreneurship knowledge does not affect the Interests of Entrepreneurship.